2013
DOI: 10.1016/j.jpowsour.2013.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics and internal phenomena of polymer electrolyte membrane fuel cell with porous flow field

Abstract: Polymer electrolyte membrane fuel cells (PEFC) with a porous flow field have been proposed as an alternative to cells with gas flow channels. In this study, the basic characteristics of a PEFC with a porous flow field are identified experimentally. It is shown that stable operation is maintained under conditions at high current density and low stoichiometric ratios of the cathode air, but that operation with low relative humidity gases is difficult in the porous type cell. To clarify the detailed causes of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 14 publications
4
13
0
Order By: Relevance
“…The porous materials provide better drainage of the condensed water that is advantageous at high current densities (Tabe et al, 2013;Kozakai et al, 2016), and more uniform reactant gas distribution compared to the FFPs with channels (Hontañón et al, 2000). The foams, meshes and fibrous porous materials have been tested as candidates for the FFP (Kumar and Reddy, 2003b;Tang et al, 2010).…”
Section: Porous Type Ffpsmentioning
confidence: 99%
“…The porous materials provide better drainage of the condensed water that is advantageous at high current densities (Tabe et al, 2013;Kozakai et al, 2016), and more uniform reactant gas distribution compared to the FFPs with channels (Hontañón et al, 2000). The foams, meshes and fibrous porous materials have been tested as candidates for the FFP (Kumar and Reddy, 2003b;Tang et al, 2010).…”
Section: Porous Type Ffpsmentioning
confidence: 99%
“…As of present, the reported flow fields which have been conceived for application in the field of fuel cells are numerous. Some of the options include serpentine, parallel, pin-type, integrated, spiral, bio-inspired and porous flow fields [15][16][17][18][19]. A particular geometry possesses a number of parameters such as channel width, depth, the shape of cross-section, the number of turns/channels, taper ratios, and path length [20][21][22][23][24].…”
Section: Porositymentioning
confidence: 99%
“…Recent studies have used metal foam as fuel cell flow fields to improve the PEFC performance, especially in terms of gas distribution and water management [32][33][34][35][36][37][38][39][40][41][42]. These studies have shown that the properties of metal foam, including high porosity, low permeability, and high tortuosity [33,40], homogenize the flow distribution and improve water management.…”
Section: Introductionmentioning
confidence: 99%